Динаміка процесів в асинхронному двигуні з послідовно увімкненими конденсаторами - Маляр, В.С.; Мадай, В.С.; Добушовська, І.А. (Електротехніка і електромеханіка, 2015)
Розглядається проблема математичного моделювання динамічних режимів асинхронних двигунів з поздовжньоємнісною компенсацією реактивної потужності. В основу алгоритму розрахунку покладено математичну модель асинхронного двигуна високого рівня адекватності, в якій враховується насичення та витіснення струму. Рассматривается проблема математического моделирования динамических режимов асинхронных двигателей с продольно-емкостной компенсацией реактивной мощности. В основу алгоритма расчета положена математическая модель асинхронного двигателя высокого уровня адекватности, в которой учитывается насыщение и вытеснение тока. Purpose. Development of mathematical model for calculation of starting modes of asynchronous motor connected in series with capacitors. Method. Mathematical modeling of dynamic modes of asynchronous motors with lateral capacitor compensation of reactive power. Results. The calculation algorithm and results of mathematic modeling of processes during starting modes of asynchronous motor feeding from the network through capacitors connected in series are presented. It is shown that for some values of capacitance the self-excitation processes and subharmonic oscillations can appear. Scientific novelty. Mathematic modeling and research of processes in asynchronous motor under its feeding through capacitors is carried out for the first time. The calculation algorithm is based on the mathematical model of asynchronous motor with high level of adequacy, which takes into account the magnetic core saturation and the current displacement in limbs of the rotor. Practical implication. Developed mathematical model makes it possible to investigate the possibility of self-excitation modes appearing in condition of their feeding from line with lateral compensation of reactance in order to avoid the negative effects typical for them.